2011
DOI: 10.1186/1475-2875-10-182
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of multi-antigen AMA1-based vaccines formulated with CoVaccine HT™ and Montanide ISA 51 in rhesus macaques

Abstract: BackgroundIncreasing the breadth of the functional antibody response through immunization with Plasmodium falciparum apical membrane antigen 1 (PfAMA1) multi-allele vaccine formulations has been demonstrated in several rodent and rabbit studies. This study assesses the safety and immunogenicity of three PfAMA1 Diversity-Covering (DiCo) vaccine candidates formulated as an equimolar mixture (DiCo mix) in CoVaccine HT™ or Montanide ISA 51, as well as that of a PfAMA1-MSP119 fusion protein formulated in Montanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…However, this approach failed to broaden inhibitory-antibody responses towards common epitopes and had a negative effect of reducing the overall inhibitory activity of vaccine-induced antibodies [47]. Another approach being developed in an effort to overcome antigenic diversity is the generation of synthetic AMA1 sequences (DiCo) that aim to represent the majority of AMA1 diversity in three synthetic alleles, giving equal weighting to all polymorphic sites [48][49]. Initial reports suggest that this may generate broad growth-inhibitory activity; however, to date, only a small number of different isolates has been tested for inhibition by anti-DiCo antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach failed to broaden inhibitory-antibody responses towards common epitopes and had a negative effect of reducing the overall inhibitory activity of vaccine-induced antibodies [47]. Another approach being developed in an effort to overcome antigenic diversity is the generation of synthetic AMA1 sequences (DiCo) that aim to represent the majority of AMA1 diversity in three synthetic alleles, giving equal weighting to all polymorphic sites [48][49]. Initial reports suggest that this may generate broad growth-inhibitory activity; however, to date, only a small number of different isolates has been tested for inhibition by anti-DiCo antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Dutta and his colleagues also found that a mixture of 4 allelic forms of AMA1 could induce strain-transcending antibodies (S. Dutta, personal communication). An alternative approach to overcome the polymorphic nature of AMA1 has been tested (31)(32)(33). In this approach, animals were immunized with three recombinant diversity-covering (DiCo) AMA1 proteins, which were designed to cover maximal numbers of polymorphisms in 355 sequences when all of the 3 were taken together.…”
Section: Figmentioning
confidence: 99%
“…Rabbits immunized with a mixture of the three AMA1 DiCo proteins (D1, D2, and D3 in Figure 2) produced antibodies that recognized a panel of three natural AMA1 variants in ELISA and functional assays similar to the FVO antibodies titers obtained using a homologous (FVO) immunization regime [16]. Rabbit antibodies to the DiCo mixture significantly inhibited red blood cell (RBC) invasion by five different parasite strains (FCR3, 3D7, HB3, CAMP, and 7G8) [28], and a mixture of three AMA1 DiCo proteins formulated in potent adjuvants was subsequently shown to induce high (functional) responses to a panel of three laboratory strains in nonhuman primates [29]. Of note here is that none of the DiCo proteins had a glutamic acid at the previously defined immunodominant position 197 [19], yet growth inhibition against the 3D7 strain harboring glutamic acid at position 197 was comparable to inhibition of assay strains with a homologous amino acid at position 197 (e.g.…”
Section: Covering Polymorphismmentioning
confidence: 93%